2009
DOI: 10.1021/ja9047043
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Testing of Difluoroboron-Derivatized Curcumins as Near-Infrared Probes for in Vivo Detection of Amyloid-β Deposits

Abstract: Amyloid-β (Aβ) deposits have been identified as key players in the progression of Alzheimer’s disease (AD). Recent evidence indicates that the deposits probably precede and induce the neuronal atrophy. Therefore, methods that enable monitoring the pathology before clinical symptoms are observed would be beneficial for the early AD detection. Here, we report the design, synthesis, and testing of a curcumin derivatized near infrared (NIR) probe CRANAD-2. Upon interacting with Aβ aggregates, CRANAD-2 undergoes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
421
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 436 publications
(436 citation statements)
references
References 42 publications
13
421
1
1
Order By: Relevance
“…As a brainimaging probe, CRANAD-3 must meet several requirements that include proper lipophilicity (log P) and reasonable penetration of the brain-blood barrier (BBB) (47). We found that log P for CRANAD-3 was 2.50, which is reasonable for brain imaging.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As a brainimaging probe, CRANAD-3 must meet several requirements that include proper lipophilicity (log P) and reasonable penetration of the brain-blood barrier (BBB) (47). We found that log P for CRANAD-3 was 2.50, which is reasonable for brain imaging.…”
Section: Resultsmentioning
confidence: 90%
“…In our previous studies, we showed that CRANAD-2, a curcumin-based NIRF imaging probe, can differentiate between 19-mo-old wild-type and transgenic mice by in vivo NIRF imaging (47). CRANAD-2 could be considered a "smart" probe because it displayed a significant increase in fluorescence intensity, an emission blue shift, a lifetime change, and quantum yield improvement upon interacting with insoluble Aβ aggregates (47). However, we found that CRANAD-2 was not able to detect soluble Aβ species (46).…”
Section: Resultsmentioning
confidence: 99%
“…600−800 nm), 7 where tissue scattering and absorption is lowest, 10 (3) large Stokes shift, (4) ability to modulate fibril aggregation, (5) minimum interference from human serum albumin (HSA) binding, (6) a small molecular size, which enables the small molecule to cross the BBB, and (7) low toxicity. [6][7][8][9]11 As a starting point, we noticed that several styryl derivatives, designed by Li et al to improve the pharmacokinetic properties of CR and ThT, were employed as AD imaging agents in vivo. 12 Interestingly, some of them were also found to be active against prion replication in infected cells.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…600−800 nm), 7 where tissue scattering and absorption is lowest, 10 (3) large Stokes shift, (4) ability to modulate fibril aggregation, (5) minimum interference from human serum albumin (HSA) binding, (6) a small molecular size, which enables the small molecule to cross the BBB, and (7) low toxicity. [6][7][8][9]11 …”
mentioning
confidence: 99%
“…However, there have been fewer reports regarding the development of fluorescent probes than PET probes despite their significance, although AOI-987, 29 NIAD-4, 30 CRANAD-2, 32 ANCA-11, 35 and BMAOI 36 have been reported for the imaging of Aβ plaques.…”
mentioning
confidence: 99%